The Concept of Piercing the Corporate Veil in the Polish Capital Companies Law - Zbigniew KUNIEWICZ (Communications of International Proceedings, 2020)
The issue in question which is the subject of the research analysis in this paper is not regulated in the Polish legal system. The consequence of the organizational structure adopted by the legislator involves a clear separation of the company from its shareholders. This separation is demonstrated in the personal, organizational and material sphere. From the point of view of the main theme of these reflections, the most important aspect of separate personhood of a capital company is to adopt the principle of non-liability of shareholders for the company’s obligations. Company’s debts are its own debts for which it is fully liable. For shareholders the company's debts are debts of a third party. Shareholders are obliged to make contributions to the company and only to this extend do they bear the economic risk of participation in the company which involves the likelihood of losing the contributed resources. Even though the principle of shareholders’ non-liability for the capital company’s obligations results from the company’s separate personhood, the legislator decided to express it directly in legal provisions. It is worth adding at that that shareholders’ non-liability for the company’s obligations is treated as a fundamental principle inscribed in the construction of capital companies. The above-mentioned comments trigger a question of whether the principle of shareholders’ non-liability for obligations of a capital company is absolute or whether it may be lifted in certain circumstances. There are increasingly frequent opinions coming from legal scholars and the judicature, inspired mainly by the views of the Western legal commentary which questions the absolute nature of the discussed principle. It is therefore pointed out that in certain cases it is necessary to disregard the company’s separate personhood and impose liability for its obligations on its shareholders. These situations are treated as exceptions and boil down to cases where the form of the company’s legal personality was used to circumvent statutory bans or to achieve benefits contrary to principles of community life. The method of interpretation of applicable laws in an apragmatic approach was employed in preparing this paper. Conclusions that derive from the analysis have the nature of postulates. They express a need for a normative regulation of the concept of the so-called piercing of the corporate veil in capital companies since the existing legal regulations provide a doubtful basis for applying this structure.
Keywords: capital companies; shareholders’ liability for company’s obligations.